Academic Writing and Culture: An Overview of Differences between English, French and German - Siepmann, Dirk (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractThis article provides a critical overview of recent research on cross-cultural divergences between English, French and German academic writing, demonstrating its relevance to translation. The author starts by discussing Galtung’s notion of culture-specific intellectual styles. He then explores the relationship between composition teaching and writing style. This is followed by a detailed discussion of cross-language comparisons of various text types which lend evidence to significant differences between the linguacultures under survey. The resultant plurality of linguacultures, the author goes on to argue, must be preserved as a value in itself, and merits special attention on the part of the translator.